On equations of Cosserat-type shells - Altenbach, Holm; Eremeyev, Victor Anatol'evich (Computational Continuum Mechanics, 2009)
A review of the family of the Cosserat-type nonlinear shell theories is presented. Starting with a general directed deformable surface model withpdirectors, we consider different elastic shell models using the direct approach. For derivation of the governing equations, we use the principle of virtual work and the principle of material frame-indifference applied to the surface density of a strain function. We discuss the interrelation between the most popular models, such as the directed surface model with one deformable director, the micromorphic and micropolar shell models, and the Timoshenko-Reissner-Mindlin model.
Keywords: Cosserat shell; micropolar medium; micromorphic medium; micropolar shell; nonlinear elasticity